RhoA is dispensable for axon guidance of sensory neurons in the mouse dorsal root ganglia - Leslie, Jennifer R.; Imai, Fumiyasu; Zhou, Xuan; Lang, Richard A.; Zheng, Yi; Yoshida, Yutaka (Frontiers in Molecular Neuroscience, 2012)
RhoA, a member of Rho family small GTPases, has been shown to play important roles in axon guidance. However, it remains unknown whether RhoA is actually required for any axon guidance events in vivo in the mammalian nervous system. To date, the physiological function of RhoA in axon guidance has not yet to be determined genetically in animals. Here we show that RhoA mRNA is strongly expressed by sensory neurons in the dorsal root ganglia during mouse embryogenesis. We have deleted RhoA in sensory neurons of the dorsal root ganglia using RhoA-floxed mice under the Wnt1-Cre driver in which Cre is strongly expressed in sensory neurons. Peripheral projections of sensory neurons appear normal and there are no detectable defects in the central projections of both cutaneous and proprioceptive sensory neurons in RhoAf/f; Wnt1-Cre mice. Furthermore, a co-culture assay using control or RhoA-deficient dorsal root ganglia explants and 293T cells expressing semaphorin3A reveals that RhoA is not required for semaphorin3A-mediated axonal repulsion of sensory neurons. Expression of RhoC, a closely related family member, is increased in RhoA-deficient sensory neurons and may play a compensatory role in this context. Taken together, these genetic studies demonstrate that RhoA is dispensable for peripheral and central projections of sensory neurons in the dorsal root ganglia.